Excessive Checking in Obsessive-Compulsive Disorder: Neurochemical Correlates Revealed by 7T Magnetic Resonance Spectroscopy - Biria, Marjan; Banca, Paula; Keser, Engin; Healy, Mairead P.; Sawiak, Stephen J.; de Souza, Ana Maria Frota Lisboa Pereira; Aleya, A Marzuki *; Sule, Akeem; Robbins, Trevor W. (Elsevier, 2024)
Background Compulsive checking, a common symptom of obsessive-compulsive disorder (OCD), has been difficult to capture experimentally. Therefore, determination of its neural basis remains challenging despite some evidence suggesting that it is linked to dysfunction of cingulostriatal systems. This study introduces a novel experimental paradigm to measure excessive checking and its neurochemical correlates.